Cost-effectiveness analysis of EGFR mutation testing and gefitinib as first-line therapy for non-small cell lung cancer. Issue 1 (October 2015) - Narita, Yusuke; Matsushima, Yukiko; Shiroiwa, Takeru; Chiba, Koji; Nakanishi, Yoichi; Kurokawa, Tatsuo; Urushihara, Hisashi
Highlights: Cost-effectiveness of first-line gefitinib therapy with EGFR testing is examined using Markov model. Combination use of gefitinib and EGFR testing for NSCLC is cost-effective in Japan. Our results are robust with several sensitivity and scenario analyses. Abstract: Objectives: The combination use of gefitinib and epidermal growth factor receptor (EGFR) testing is a standard first-line therapy for patients with non-small cell lung cancer (NSCLC). Here, we examined the cost-effectiveness of this approach in Japan. Materials and methods: Our analysis compared the 'EGFR testing strategy', in which EGFR mutation testing was performed before treatment and patients with EGFR mutations received gefitinib while those without mutations received standard chemotherapy, to the 'no-testing strategy, ' in which genetic testing was not conducted and all patients were treated with standard chemotherapy. A three-state Markov model was constructed to predict expected costs and outcomes for each strategy. We included only direct medical costs from the healthcare payer's perspective. Outcomes in the model were based on those reported in the Iressa Pan-Asia Study (IPASS). The incremental cost-effectiveness ratio (ICER) was calculated using quality-adjusted life-years (QALYs) gained. Sensitivity and scenario analyses were conducted. Results: The incremental cost and effectiveness per patient of the 'EGFR testing strategy' compared to the 'no-testing strategy' was estimated to be approximately JP¥122, 000 (US$1180; US$1 = JP¥104 as of February 2014) and 0.036 QALYs. The ICER was then calculated to be around JP¥3.38 million (US$32, 500) per QALY gained. These results suggest that the 'EGFR testing strategy' is cost-effective compared with the 'no-testing strategy' when JP¥5.0 million to 6.0 million per QALY gained is considered an acceptable threshold. These results were supported by the sensitivity and scenario analyses. Conclusion: The combination use of gefitinib and EGFR testing can be considered a cost-effective first-line therapy compared to chemotherapy such as carboplatin–paclitaxel for the treatment for NSCLC in Japan.